Preparation of biomass carbon-based material and application of biomass carbon-based material in catalyzing nitrobenzene to prepare aniline

By using biomass carbon-based materials prepared by soybean rods and combined with the use of hydrazine hydrate, the problems of complex catalyst preparation and safety risks in the prior art are solved, and the effect of efficient and safe catalytic nitrobenzene to aniline is achieved.

CN119819345APending Publication Date: 2025-04-15JILIN INST OF CHEM TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510006052.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing biomass carbon materials need to be doped or loaded with other substances in the process of catalyzing the production of nitrobenzene, which leads to complex and high cost. The commonly used reducing agent sodium borohydride is toxic and flammable and explosive, affecting industrial production safety.

Method used

Soybean rods are used as precursors to prepare biomass carbon-based materials through pre-carbonization, hydrothermal treatment and carbonization treatment. They contain nitrogen elements themselves without additional doping. Hydroxyhydrate is used as a reducing agent. The conditions are mild, safe and reliable.

Benefits of technology

It has achieved efficient catalytic catalytic nitrobenzene to aniline under mild conditions. The catalyst has good catalytic activity, efficiency and stability, and can be reused many times. It is suitable for industrial production and reduces production costs and safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819345A_ABST
    Figure CN119819345A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of a biomass carbon-based material and application of the biomass carbon-based material in catalyzing nitrobenzene to prepare aniline, and relates to the technical field of new materials and catalysis. The method comprises the following steps: S01, preparation of a pre-carbonized sample: taking soybean stems, cutting short, cleaning, drying and crushing, putting soybean stem powder into a tubular furnace, pre-carbonizing by taking nitrogen as a shielding gas, and naturally cooling to room temperature to obtain the pre-carbonized sample; s02, preparation of a hydrothermal sample: adding deionized water into the pre-carbonized sample, performing magnetic stirring to obtain turbid liquid, pouring the turbid liquid into a reaction kettle, performing hydrothermal treatment, and performing cooling, suction filtration, washing and vacuum drying after the hydrothermal treatment to obtain the hydrothermal sample. In the aspect of catalyst preparation, the raw material soybean stalks are biomass renewable resources, contain nitrogen elements, do not need to be additionally doped with other substances, and are cheap and easy to obtain, the preparation process is simple, the preparation conditions are easy to control, the synthesis route is simple, and the method is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new materials and catalytic technology, and relates to national key development industries such as biomass recycling, agricultural product processing, energy conservation and environmental protection, and fine chemicals. Specifically, it relates to the preparation of a biomass carbon-based material and its application in catalyzing nitrobenzene to produce aniline. Background Art

[0002] The chemoselective hydrogenation of nitroaromatic compounds is an important chemical process because the hydrogenation products, aromatic amines, are raw materials for the synthesis of drugs, pesticides, rubber chemicals, photosensitive chemicals, surfactants, and various industrially valuable raw materials. Since the nitro group of nitroaromatic compounds is very inert, spontaneous hydrogenation reactions can hardly occur using reducing agents. Therefore, the conversion of nitro groups to amino groups always occurs under the action of catalysts. Aniline is an important raw material for many chemical products such as pharmaceuticals, dyes, pesticides and polymers, and is one of the most important amine substances. About 85% of aniline in the world is produced by catalytic hydrogenation of nitrobenzene. Compared with the harsh reaction conditions required for gas-phase hydrogenation, liquid-phase hydrogenation can be carried out efficiently under milder and easier-to-handle conditions. Due to its wide range of applications and low pollution, it is very consistent with the development direction of green chemical industry.

[0003] Biomass material is a renewable natural resource with the advantages of high yield, low cost, wide source, and green environmental protection. In addition, it has a unique structure and rich heteroatoms (nitrogen, oxygen, phosphorus, sulfur, etc.), which makes it have good prospects in the application of preparing catalysts. More and more researchers are focusing on using waste biomass to synthesize low-cost carbon materials with unique porous structures. Many different types of biomass materials, such as sawdust, mulberry leaves, rice husks and mugwort, have been used as precursors for producing porous carbon or heteroatom-doped carbon with good catalytic performance.

[0004] Patent ZL2022102180234 discloses a preparation method of boron, nitrogen and phosphorus co-doped straw-based biomass carbon with honeycomb pores and its application as a supercapacitor electrode material. The invention uses straw as raw material, and boric acid, urea and disodium hydrogen phosphate as cheap boron source, nitrogen source and phosphorus source respectively. After activation with potassium hydroxide, it is treated at high temperature under the protection of nitrogen atmosphere, and then pickled and dried to finally obtain boron, nitrogen, phosphorus and other multi-element co-doped biomass porous carbon; Patent ZL2019101931357 discloses a heteroatom-doped biomass-based carbon material, preparation method and application. The invention uses dry radish powder as a biomass carbon source, and prepares a heteroatom-doped biomass-based carbon material by heteroatom doping and high-temperature roasting. It is used in the catalytic oxidation of styrene, the catalytic oxidation of ethylbenzene and the catalytic hydrogenation of nitroaromatic compounds. In the reaction, sodium borohydride is used as a reducing agent in the catalytic hydrogenation reaction of p-nitrophenol; Patent ZL2019109798946 discloses the preparation of a metal-loaded catalyst with a nitrogen-doped carbon-based carrier derived from bean dregs as a carrier and a method for catalyzing the hydrogenation and deoxygenation of p-nitrophenol. The bean dregs are subjected to low-temperature roasting, potassium hydroxide mixing, and high-temperature roasting to obtain a nitrogen-carbon carrier. After loading the metal, a metal-loaded nitrogen-carbon material catalyst is obtained, and sodium borohydride is used as a reducing agent to catalyze p-nitrophenol; although the biomass carbon materials prepared in the above patents have good catalytic properties, they all require additional doping or loading of other substances, which makes the production process more cumbersome and increases the production cost; at the same time, the sodium borohydride reducing agent is toxic and irritating, has high transportation and storage requirements, and has high chemical reactivity, is flammable and explosive, and is not conducive to industrial production safety.

[0005] With the cultivation and utilization of soybeans, a large amount of soybean stalks are produced. Currently, the utilization rate of soybean stalks is less than 3%. These soybean stalks are usually burned or discarded, which brings great pressure to the environment. Since soybean stalks have a honeycomb epidermis and ground tissue that can be inherited and converted into porous carbon with a 3D layered structure, soybean stalks can be used as a precursor to prepare porous carbon materials. Soybean stalks are different from other biomass materials. Soybean rhizobium is a bacterium that forms nodules with the roots of leguminous plants. Rhizobia parasitize on the roots of soybean stalks to form nodules. Rhizobia can convert nitrogen in the air into nitrogen that can be absorbed by plants, providing more nitrogen nutrition for soybean crop plants. Soybean stalks are rich in nitrogen and are suitable for the preparation of in situ nitrogen-doped carbon materials without the need for additional doping. The utilization of waste biomass straw has not only economic value but also environmental value. Exploring the preparation of biomass carbon material catalysts with soybean stalks as precursors is of great research value and application prospects.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a preparation method of a biomass carbon-based material and its application in catalyzing nitrobenzene to produce aniline, and solve the problems raised in the above-mentioned background technology.

[0008] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0009] A preparation method of a biomass carbon-based material comprises the following steps:

[0010] S01: Preparation of pre-carbonized samples: soybean stalks were cut short, cleaned, dried, and crushed, and the soybean stalk powder was placed in a tube furnace for pre-carbonization with nitrogen as the protective gas, and naturally cooled to room temperature to obtain pre-carbonized samples; wherein, the pre-carbonization target temperature was 300-500°C, the time was 2-4h, and the pre-carbonization heating rate was 5°C / min;

[0011] S02: Preparation of hydrothermal samples: the pre-carbonized sample is added with deionized water and magnetically stirred to obtain a suspension, which is poured into a reactor for hydrothermal treatment. After the hydrothermal treatment, the sample is cooled, filtered, washed, and vacuum dried to obtain a hydrothermal sample; wherein the hydrothermal treatment temperature is 110-180°C, the time is 2-12h, the vacuum drying temperature is 60-90°C, the time is 10-12h, and the magnetic stirring time is 10-12h;

[0012] S03: Mixing the hydrothermal sample with the KOH solution: Evenly mix the hydrothermal sample with the KOH solution, dry and grind to obtain a ground sample; wherein the ratio of the hydrothermal sample to the KOH solution is 1g:(0.9-4.5)mol / L, and the drying temperature is 60-90°C;

[0013] S04: Preparation of biomass carbon-based materials: Take the ground sample, put it into a tube furnace, and use nitrogen as a protective gas for carbonization treatment. The carbonized product is thoroughly washed with hydrochloric acid solution and deionized water to neutrality, and vacuum dried to obtain a black powder carbon-based material; wherein the carbonization treatment includes:

[0014] In the first carbonization stage, the carbonization temperature rise rate is 8-12°C / min, the carbonization temperature is 350-450°C, and the carbonization time is 50-70min;

[0015] In the second carbonization stage, the carbonization temperature rise rate is 3-8°C / min, the carbonization temperature is 500-900°C, and the carbonization time is 110-130min.

[0016] A biomass carbon-based material is used in catalyzing nitrobenzene to produce aniline, comprising:

[0017] Catalytic experiment, the specific method is: the carbon-based material is uniformly dispersed in the solvent, and then the reactant nitrobenzene and the reducing agent hydrazine hydrate are added, heated and magnetically stirred, and samples are taken after a period of reaction, and detected by gas chromatography, and the conversion rate of nitrobenzene and the selectivity and yield of aniline are calculated; wherein the solvent is any one of acetonitrile, ethanol, and cyclohexane, the addition ratio of the carbon-based material to nitrobenzene and hydrazine hydrate is (5-15) mg:0.5 mmol:(2-5 mmol), and the reaction temperature is 60-80°C, and the reaction time is 0.1-4h;

[0018] The specific method of the recycling experiment is: the used carbon-based materials are repeatedly washed and then recycled after vacuum drying;

[0019] The experiment was interrupted. The specific method was as follows: after the first experiment was interrupted for sampling, the catalyst was filtered out while hot, the catalyst was washed with anhydrous ethanol for multiple times, the washing liquid and the filtrate were collected, the reaction was continued under the original experimental conditions, and the stability of the carbon-based material was detected by gas chromatography using samples.

[0020] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:

[0021] (1) In the catalyst preparation of the present invention, the raw material soybean stalk is a renewable biomass resource, which contains nitrogen and does not need to be doped with other substances. It is cheap and easy to obtain, the preparation process is simple, the preparation conditions are easy to control, the synthesis route is simple, and it is suitable for industrial production.

[0022] (2) In the catalytic hydrogenation reaction of nitrobenzene, the conditions required for the catalytic system of the present invention are mild, avoiding the danger of high temperature and high pressure. Compared with other reducing agents, hydrazine hydrate has a lower risk of explosion, is convenient to transport and store, and has low corrosiveness to experimental equipment. The catalyst has good catalytic activity, catalytic efficiency and stability, and can be reused multiple times without reducing the catalytic effect. It has application potential in the fields of industrial catalysts and fine chemical synthesis.

[0023] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0025] Attached Figure 1 is a scanning electron microscope image of SSC-700;

[0026] Attached Figure 2N2 adsorption-desorption curve (a) and pore distribution curve (b) of SSC-700;

[0027] Attached Figure 3 This is the X-ray photoelectron spectrum of SSC-700;

[0028] Attached Figure 4 is the Raman spectrum of SSC-700;

[0029] Attached Figure 5 It is a line graph of the hydrogenation reaction of nitrobenzene catalyzed by SSC-700;

[0030] Attached Figure 6 This is a bar chart of the cyclic experiment of nitrobenzene hydrogenation reaction catalyzed by SSC-700.

[0031] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0032] The present invention will now be described in further detail with reference to the accompanying drawings.

[0033] The purpose of the present invention is to provide a method for preparing a green, economical, efficient, stable and reusable carbon-based material for catalyzing the hydrogenation reaction of nitrobenzene using biomass as a precursor. The material is sourced from waste biomass and has low cost; it contains nitrogen itself and does not require additional doping with other substances; nitrobenzene can be efficiently reduced under mild conditions; and it has high selectivity for aniline.

[0034] In order to achieve the above object, the present invention adopts the following technical solution:

[0035] First embodiment: Please refer to Figure 1-6 As shown, in this embodiment, a method for preparing a biomass carbon-based material is provided, comprising the following steps:

[0036] S01: Preparation of pre-carbonized samples: Soybean stalks are cut short, cleaned, dried, and crushed. The soybean stalk powder is placed in a tubular furnace and pre-carbonized with nitrogen as a protective gas. The pre-carbonized sample is naturally cooled to room temperature to obtain a pre-carbonized sample. The pre-carbonization target temperature is 300-500°C, the time is 2-4h, and the pre-carbonization heating rate is 5°C / min. Pre-carbonization is used to remove impurities such as bio-oil in biomass, leaving biomass carbon.

[0037] S02: Preparation of hydrothermal samples: Add deionized water to the pre-carbonized sample and stir it magnetically to obtain a suspension, pour it into a reactor for hydrothermal treatment, cool it, filter it, wash it, and dry it under vacuum to obtain a hydrothermal sample; wherein the hydrothermal treatment temperature is 110-180°C, the time is 2-12h, the vacuum drying temperature is 60-90°C, the time is 10-12h, and the magnetic stirring time is 10-12h; the hydrothermal sample has the effect of stabilizing the structure of the carbon material, which helps to retain the impurity elements such as N and O in the carbon material and improve the catalytic performance;

[0038] S03: Mixing the hydrothermal sample with the KOH solution: Evenly mix the hydrothermal sample with the KOH solution, dry and grind to obtain a ground sample; wherein the ratio of the hydrothermal sample to the KOH solution is 1g:(0.9-4.5)mol / L, and the drying temperature is 60-90°C; KOH reacts with the carbon material to promote the growth of carbon pores and increase the specific surface area;

[0039] S04: Preparation of biomass carbon-based materials: Take the ground sample, put it into a tube furnace, and use nitrogen as a protective gas for carbonization treatment. The carbonized product is thoroughly washed with hydrochloric acid solution and deionized water to neutrality, and vacuum dried to obtain a black powder carbon-based material; wherein the carbonization treatment includes:

[0040] In the first carbonization stage, the carbonization temperature rise rate is 8-12°C / min, the carbonization temperature is 350-450°C, and the carbonization time is 50-70min;

[0041] In the second carbonization stage, the carbonization temperature rises at a rate of 3-8°C / min, the carbonization temperature is 500-900°C, and the carbonization time is 110-130min. Through two carbonization treatment stages, the carbonization temperature can affect the graphitization degree of the material, thereby affecting the catalytic performance of the material for hydrogenation of nitrobenzene; at the same time, the nitrogen species in the material will also affect the catalytic performance.

[0042] In the catalyst preparation of the present invention, the raw material soybean stalk is a renewable biomass resource, contains nitrogen itself, does not need to be doped with other substances, is cheap and easy to obtain, has a simple preparation process, is easy to control preparation conditions, and has a simple synthesis route, which is suitable for industrial production.

[0043] Second embodiment: A preparation method of a biomass carbon-based material comprises the following steps:

[0044] (1) Preparation of pre-carbonized samples: Soybean stalks were cut short, cleaned, dried at 80 °C, and crushed. The soybean stalk powder was placed in a tube furnace, and 30 mL / min of nitrogen was used as a protective gas. The temperature was increased to 350 °C, 400 °C, and 450 °C at a rate of 5 °C / min. The samples were pre-carbonized for 2 h and naturally cooled to room temperature to obtain pre-carbonized samples. Pre-carbonization was used to remove impurities such as bio-oil in biomass, leaving biomass carbon.

[0045] (2) Preparation of hydrothermal samples: 1.0 g of pre-carbonized sample was added with 30 mL of deionized water and magnetically stirred for 12 h. The obtained suspension was poured into a reactor for hydrothermal treatment for 12 h at a hydrothermal temperature of 120 ° C, 150 ° C and 180 ° C. The sample was cooled, filtered, washed and vacuum dried at 80 ° C for 12 h to obtain a hydrothermal sample. The hydrothermal sample has the effect of stabilizing the structure of the carbon material, which helps to retain impurity elements such as N and O in the carbon material and improve the catalytic performance.

[0046] (3) Mixing the hydrothermal sample with KOH solution: 1.0 g of the hydrothermal sample and 20 mL of KOH solution (with concentrations of 0.9 mol / L, 2.7 mol / L, and 4.5 mol / L, respectively) were mixed evenly, dried at 80 °C, and then ground; KOH reacts with the carbon material to promote the growth of carbon pores and increase the specific surface area;

[0047] (4) Preparation of SSC-X: The above samples were taken, placed in a tubular furnace, and carbonized with 30 mL / min nitrogen as the protective gas. The carbonization temperatures were 600°C, 700°C, and 800°C, and the carbonization time was 2 h. The carbonized products were thoroughly washed with 1 mol / L hydrochloric acid solution and deionized water until neutral, and vacuum dried to obtain black powder carbon-based materials, named SSP-350, SSP-400, SSP-450, SSH-120, SSH-150, SSH-180, SSK-1:1, SSK-1:3, SSK-1:5, SSC-600, SSC-700, and SSC-800.

[0048] In the catalyst preparation of the present invention, the raw material soybean stalk is a renewable biomass resource, contains nitrogen itself, does not need to be doped with other substances, is cheap and easy to obtain, has a simple preparation process, is easy to control preparation conditions, and has a simple synthesis route, which is suitable for industrial production.

[0049] Third embodiment: Based on the catalyst preparation described in the first and second embodiments, the present invention studies the catalytic performance of carbon-based materials in the nitrobenzene hydrogenation reaction. Figure 1-6 As shown, an application of a biomass carbon-based material in catalyzing nitrobenzene to produce aniline comprises:

[0050] Catalytic experiment, the specific method is: the carbon-based material is evenly dispersed in the solvent, and then the reactant nitrobenzene and the reducing agent hydrazine hydrate are added, heated and magnetically stirred, and samples are taken after a period of reaction, and detected by gas chromatography, and the conversion rate of nitrobenzene and the selectivity and yield of aniline are calculated; wherein, the solvent is any one of acetonitrile, ethanol, and cyclohexane, and the solvent with strong polarity will form competitive adsorption with nitrobenzene on the catalyst surface, thereby resulting in reduced catalytic efficiency and reduced reaction conversion rate, and the solvent with weak polarity will increase the reaction conversion rate, the addition ratio of the carbon-based material to nitrobenzene and hydrazine hydrate is (5-15) mg:0.5 mmol:(2-5 mmol), and the reaction temperature is 60-80 ° C, and the reaction time is 0.1-4h. Properly increasing the amount of catalyst will increase the conversion rate of nitrobenzene, and hydrazine hydrate is the hydrogen source of the reaction. Compared with hydrogen, hydrazine hydrate is green and environmentally friendly, has a small risk of explosion, and is easy to transport and store;

[0051] The experiment was interrupted. The specific method was as follows: after the first experiment was interrupted for sampling, the catalyst was filtered out while hot, the catalyst was washed with anhydrous ethanol for multiple times, the washing liquid and the filtrate were collected, the reaction was continued under the original experimental conditions, and the stability of the carbon-based material was detected by gas chromatography using samples.

[0052] The specific method of the recycling experiment is: the used carbon-based materials are repeatedly washed and then recycled after vacuum drying;

[0053] Specifically, a catalyst SSC-X, 4 mL of an organic solvent, 0.5 mmol of nitrobenzene, and 2-5 mmol of hydrazine hydrate are added to a round-bottom flask equipped with a reflux condenser and a magnetic stirrer, and the mixture is heated and magnetically stirred. After a period of reaction, a sample is taken, and after filtering through a filter membrane, the conversion rate of nitrobenzene and the yield of aniline are detected by gas chromatography.

[0054] The gas phase detection conditions were as follows: vaporization chamber 240°C, detector 280°C, initial column temperature 80°C, heating to 160°C at 10°C / min, maintained for 1 min, then heating to 240°C at 20°C / min, maintained for 10 min.

[0055] Table 1 Examples 1-12 reflect the catalytic effect of catalysts prepared under different conditions on nitrobenzene hydrogenation reaction; the reaction conditions of Examples 1-12 are 15 mg catalyst, nitrobenzene and hydrazine hydrate molar ratio of 1:10, reaction temperature of 80°C, solvent ethanol of 4 mL; reaction time of 4 h; the selectivity of all catalysts for aniline is greater than 99.9%.

[0056] Table 1 Catalytic application effects of different catalysts in nitrobenzene hydrogenation reaction

[0057]

[0058] In Table 1, the pre-carbonization temperatures of Examples 1, 2, and 3 are 350, 400, and 450°C, respectively; the hydrothermal temperatures of Examples 4, 5, and 6 are 120, 150, and 180°C, respectively; the ratios of the hydrothermal sample to KOH in Examples 7, 8, and 9 are 1:0.9, 1:2.7, and 1:4.5, respectively; the carbonization temperatures of Examples 10, 11, and 12 are 600, 700, and 800°C, respectively.

[0059] Specifically, it can be seen from Examples 1, 2, and 3 that the pre-carbonization temperature in the catalyst synthesis process is different, and other preparation conditions and catalytic reaction conditions are the same. It can be seen from the experimental data that the lower the pre-carbonization temperature, the better the catalytic nitrobenzene hydrogenation reaction effect. When the pre-carbonization temperature is 300°C, the material is not completely carbonized, so the pre-carbonization temperature is selected to be 350°C.

[0060] In Examples 4, 5, and 6, except for the different hydrothermal temperatures, other preparation conditions and catalytic reaction conditions are the same. It can be seen from the experimental data that with the increase of the hydrothermal temperature, the conversion rate of the catalytic nitrobenzene hydrogenation reaction increases, but when the hydrothermal temperature rises to 180°C, the conversion rate decreases. SSH-150 with a hydrothermal temperature of 150°C has a better catalytic effect in the catalytic nitrobenzene hydrogenation reaction.

[0061] In Examples 7, 8, and 9, except for the different mixing ratios of the hydrothermal sample and the KOH solution, the other preparation conditions and catalytic reaction conditions are the same. It can be seen from the experimental data that increasing the concentration of the KOH solution is beneficial to the activation of the catalyst, and when the mixing ratio of the hydrothermal sample and the KOH solution is 1 g:4.5 mol / L, the activation effect is better.

[0062] In Examples 10, 11, and 12, except for the carbonization temperature, the other preparation conditions and catalytic reaction conditions are the same. It can be seen from the experimental data that SSC-700 has a better catalytic effect in the catalytic nitrobenzene hydrogenation reaction. The carbonization temperature will affect factors such as the graphitization degree, nitrogen species distribution, and specific surface area of ​​SSC-700, thereby affecting the catalytic performance of the material.

[0063] Examples 13-23 in Table 2 demonstrate the catalytic effect of SSC-700 on nitrobenzene hydrogenation under different reaction conditions.

[0064] Table 2 Catalytic application effect of SSC-700 in nitrobenzene hydrogenation reaction

[0065]

[0066]

[0067] In Table 2, Example 13 is a blank experiment; the solvents added in the reactions of Examples 14, 15, and 16 are acetonitrile, ethanol, and cyclohexane, respectively; the temperatures for catalyzing the hydrogenation of nitrobenzene in Examples 16, 17, and 18 are 80, 70, and 60° C., respectively; the amounts of hydrazine hydrate added in Examples 16, 19, 20, and 21 are 5, 4, 3, and 2 mmol, respectively; the amounts of SSC-700 used in Examples 21, 22, and 23 are 10, 5, and 15 mg, respectively;

[0068] Specifically, it can be seen from the experimental data of Examples 13 and 16 that: under the same experimental conditions, the hydrogenation of nitrobenzene did not react in the blank experiment, and the addition of SSC-700 material had an obvious catalytic effect on the hydrogenation reaction of nitrobenzene.

[0069] In Examples 14, 15 and 16, except for the different solvents added, other catalytic reaction conditions are the same. Experiments have found that solvents with low polarity promote the conversion of nitrobenzene. After 0.4 hours of reaction, the conversion rate of nitrobenzene in the reaction with cyclohexane as solvent is higher.

[0070] In Examples 16, 17 and 18, except for the different reaction temperatures in the catalytic reaction, other catalytic reaction conditions are the same. It can be seen from the experimental data that the increase in reaction temperature is conducive to the conversion of nitrobenzene. In Example 16, the reaction temperature is 80° C., the conversion rate of nitrobenzene is 60%, and the selectivity of aniline is 100%.

[0071] In Examples 16, 19, 20 and 21, except for the different amounts of the reducing agent hydrazine hydrate, other catalytic reaction conditions are the same. It can be seen from the experimental data that when the molar ratio of nitrobenzene to hydrazine hydrate is 1:4, the conversion rate of nitrobenzene is higher.

[0072] In Examples 21, 22, and 23, except for the different amounts of the catalyst SSC-700, the other catalytic reaction conditions are the same. From the experimental data, it can be seen that in Example 23, the amount of catalyst SSC-700 added is the largest, the nitrobenzene conversion rate is the highest, and the catalytic effect is good. However, considering the cost of raw materials, the preferred amount of SSC-700 is 10 mg.

[0073] In addition, SSC-700 was tested by scanning electron microscope. Figure 1 It can be seen that SSC-700 is composed of a large number of mutually cross-linked and interpenetrating particles.

[0074] Attached Figure 2 a is the N2 adsorption-desorption curve of SSC-700. It can be observed that SSC-700 conforms to the characteristics of type I isotherm, and the specific surface area is 696m 2 ·g -1 , pore volume is 0.38cm 3 ·g -1 Attached Figure 2b is the pore size distribution curve of SSC-700. The most probable pore size is around 0.6 nm, indicating that most of the pores in the material are in micropore size.

[0075] Attached Figure 3 This is the X-ray photoelectron spectroscopy (XPS) of the SSC-700 catalyst. The sample contains C, O, and N elements (pyridinic N, pyrrolic N, graphitic N, and oxidized N).

[0076] Attached Figure 4 This is the Raman spectrum of SSC-700. As shown in the figure, the 1350cm -1 The D band at 1580 cm represents the disorder or defect structure of carbon atoms, while the -1 The G band at sp 2 Hybridized graphite carbon. The ID / IG ratio of SSC-700 is 0.73, which indicates that there are defect sites in SSC-700. Related reports have shown that the degree of defects can affect the effect of catalytic reduction reactions.

[0077] Attached Figure 5 It is a line graph showing the change of aniline yield with reaction time when catalyzing nitrobenzene hydrogenation reaction. Curve a is a line graph showing the change of aniline yield with reaction time when 10mg SSC-700 catalyst is used in 4mL cyclohexane as solvent, 2mmol hydrazine hydrate as reducing agent, and 0.5mmol nitrobenzene is hydrogenated at 80℃. Samples are taken and analyzed at 0.1h, 0.2h, 0.3h, 0.4h, 0.5h, and 0.6h of reaction. Curve b is a line graph showing the change of aniline yield with reaction time after the reaction is interrupted at 0.3h of reaction. Figure 5 The a and b curves indicate that SSC-700 has good stability in this reaction system.

[0078] Attached Figure 6 This is a bar chart of the cyclic experiment of nitrobenzene hydrogenation reaction catalyzed by SSC-700. Figure 6 It can be seen that after the catalyst has been used 8 times, the selectivity of aniline is 100% and the conversion rate of nitrobenzene is 99%, indicating that SSC-700 can be recycled at least 8 times and has good reusability.

[0079] In the aspect of catalyzing the hydrogenation reaction of nitrobenzene, the present invention requires mild conditions for the catalytic system, avoids the danger of high temperature and high pressure, and compared with other reducing agents, hydrazine hydrate has a small explosion risk, is convenient to transport and store, and has low corrosion to experimental equipment. The catalyst has good catalytic activity, catalytic efficiency and stability, can be reused for multiple times without reducing the catalytic effect, and has application potential in the fields of industrial catalysts and fine chemical product synthesis.

[0080] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.

Claims

1. A preparation method of a biomass carbon-based material, characterized in that: Includes: includes the following steps: S01: Preparation of pre-carbonized samples: Soybean stalks were cut short, cleaned, dried, and crushed. The soybean stalk powder was placed in a tube furnace and pre-carbonized using nitrogen as a protective gas. The pre-carbonized samples were naturally cooled to room temperature to obtain pre-carbonized samples. S02: Preparation of hydrothermal samples: the pre-carbonized sample is added with deionized water and magnetically stirred to obtain a suspension, which is poured into a reactor for hydrothermal treatment. After the hydrothermal treatment, the sample is cooled, filtered, washed, and vacuum dried to obtain a hydrothermal sample; S03: mixing the hydrothermal sample with the KOH solution: mixing the hydrothermal sample with the KOH solution evenly, drying and then grinding to obtain a ground sample; S04: Preparation of biomass carbon-based materials: Take the ground sample, put it into a tubular furnace, and perform carbonization treatment with nitrogen as the protective gas. The carbonized product is thoroughly washed with hydrochloric acid solution and deionized water to neutrality, and vacuum dried to obtain a black powder carbon-based material.

2. The preparation of a biomass carbon-based material according to claim 1, characterized in that: In S01, the pre-carbonization target temperature is 300-500°C, the time is 2-4h, and the pre-carbonization heating rate is 5°C / min.

3. The preparation of a biomass carbon-based material according to claim 1, characterized in that: In S02, the hydrothermal treatment temperature is 110-180°C for 2-12h, the vacuum drying temperature is 60-90°C for 10-12h, and the magnetic stirring time is 10-12h.

4. The preparation of a biomass carbon-based material according to claim 1, characterized in that: In S03, the ratio of hydrothermal sample to KOH solution is 1 g:(0.9-4.5) mol / L, and the drying temperature is 60-90°C.

5. The preparation of a biomass carbon-based material according to claim 1, characterized in that: In S04, the carbonization treatment includes: In the first carbonization stage, the carbonization temperature rise rate is 8-12°C / min, the carbonization temperature is 350-450°C, and the carbonization time is 50-70min; In the second carbonization stage, the carbonization temperature rise rate is 3-8°C / min, the carbonization temperature is 500-900°C, and the carbonization time is 110-130min.

6. Application of a biomass carbon-based material in catalyzing nitrobenzene to produce aniline, characterized in that: Including normal experiments, the specific method is: uniformly disperse the carbon-based material in the solvent, then add the reactant nitrobenzene and the reducing agent hydrazine hydrate, heat and magnetically stir, take samples after a period of reaction, detect through gas chromatography, and calculate the conversion rate of nitrobenzene and the selectivity and yield of aniline.

7. The use of a biomass carbon-based material in catalyzing nitrobenzene to produce aniline according to claim 6, characterized in that: It also includes recycling experiments, the specific method of which is: the used carbon-based materials are repeatedly washed and then recycled after vacuum drying.

8. The use of a biomass carbon-based material in catalyzing nitrobenzene to produce aniline according to claim 6, characterized in that: It also includes interruption experiments. The specific method is: after the first experiment sampling is interrupted, the catalyst is filtered out while hot, the catalyst is washed with anhydrous ethanol for many times, the washing liquid and the filtrate are collected, the reaction is continued under the original experimental conditions, and the stability of the carbon-based material is detected by gas chromatography after sampling.

9. The use of a biomass carbon-based material in catalyzing nitrobenzene to produce aniline according to claim 6, characterized in that: The solvent is any one of acetonitrile, ethanol and cyclohexane.

10. The use of a biomass carbon-based material in catalyzing nitrobenzene to produce aniline according to claim 6, characterized in that: The addition ratio of the carbon-based material to nitrobenzene and hydrazine hydrate is (5-15) mg:0.5 mmol:(2-5 mmol), the reaction temperature is 60-80° C., and the reaction time is 0.1-4 h.

Citation Information

Patent Citations

  • Heteroatom doped biomass derived hard carbon negative electrode material and preparation method thereof

    CN115385323A

  • Application of nitrogen-doped carbon material for catalyzing hydrazine hydrate to reduce nitrobenzene to prepare aniline

    CN117263808A

  • Preparation and application of recyclable nitrogen-doped carbon material for selectively catalyzing nitrobenzene hydrogenation to prepare aniline

    CN117299178A